Analysis of the Lecturer’s Interest after Attending the Workshop STEM Design-Based Learning for Lecturers - Adzima, Khaola Rachma; Sari, Nilam Novita; Khotimah, Tiara Husnul; Gusti, Valeria Yekti Kwasaning (JURNAL RISET PEMBELAJARAN MATEMATIKA SEKOLAH, 2025)
The STEM (Science, Technology, Engineering, and Mathematics) approach has been widely adopted in schools but remains underutilized in higher education. Lecturers often perceive STEM as difficult to implement due to complex subject matter, time constraints, and limited personal interest. This study examined whether participation in a professional development program, STEM Design-Based Learning for Lecturers, could enhance lecturer’s interest in STEM. The workshop was conducted over two weeks with 18 participants from the Faculty of Mathematics and Natural Sciences. Data were collected using pre- and post-questionnaires designed to measure lecturer’s interest in STEM. Validity and reliability tests confirmed the instrument’s quality. Since the normality assumption was not met, the Wilcoxon Signed Rank Test was applied to assess differences before and after the workshop. The results indicated a statistically significant improvement in interest (p = 0.001) with a large effect size (Cohen’s d = 1.266). Specifically, 15 of 18 lecturers reported increased interest, while two remained unchanged and one experienced a slight decrease. These findings demonstrate that structured STEM workshops can effectively foster enthusiasm and engagement among lecturers. The study highlights the importance of integrating STEM-focused professional development into higher education to support curriculum innovation and encourage broader adoption of STEM approaches in teaching.